The computer design of practical filter - Li, Z.; Weixi, Z. (Journal of Digital Information Management, 2013)
This paper discussed how to use computer to directly transfer the simulative low pass prototype design to all kinds of needed principles and design methods. This method's advantage is that it is very direct, and universal. So, this method is simple, convenient, practical and fast.
Keywords: Filter; Polynomial shift; Transform matrix